Augmenting scientific literacy through HOTS instruction in EFL classroom: Students’ perception - Armeria Wijaya (Concept : Community Concern for English Pedagogy and Teaching, 2022)
This paper examines students' perceptions of the current practice of using Higher Order Thinking Skills (HOTS) in the classroom to enhance their scientific literacy. The study was prompted by the traditional monotonous teaching of Sociolinguistics. Pre-observation activities revealed that students found the traditional sequence of classroom movement tedious and impractical in linguistics learning. Using students' presentations and classroom discussions as a learning strategy, which are considered low-order thinking skills, resulted in students not being engaged in the discussion. However, after learning with HOTS instructions, it was found that activities such as analyzing sociolinguistics phenomena, evaluating them, and proposing ideas for further research in the field of sociolinguistics, brought new perspectives to the learning experience. The results of the questionnaires, analyzed qualitatively, showed that students had positive perceptions of learning with HOTS instructions; their scientific literacy was competently advanced, the scientific knowledge was advantageous for their social and academic interactions, and they were able to identify connections between sociolinguistics and technology. In conclusion, English as a Foreign Language (EFL) students' scientific literacy can be enhanced through this type of instruction Keywords: Students’ Perception; Scientific Literacy; Augmenting Scientific Literacy; HOTS Instruction; EFL Classroom